ENT600 : EPTOL-lets training with EPTOL / Muhammad Amirul Ayob … [et al.] - Ayob, Muhammad Amirul; Md. Pilus, Muhammad Shahril; Abu Hasan, Mohammad Afiff Husaini; Zulhisham, Muhammad Naim; Zailani, Muhammad Azwan (2015)
The product intended is an elastic Pro-teaching tool (EPTOL). The tool is suitable for beginner basketball athlete to train and improve their technique playing during games.